Influence of Brand Image, Customer Experience, and Service Quality on Customer Loyalty of Indomaret Sirojudin, Semarang - Alit Nada Syahrani; Sandi Supaya; Saptianing (JOBS (Jurnal Of Business Studies), 2025)
The growth of retail in Indonesia, including Indomaret, faces challenges in maintaining customer loyalty despite having the largest number of outlets. The fact that Indomaret ranks second in national sales reflects a gap between expansion success and customer loyalty. This phenomenon is further supported by a pre-survey conducted in Semarang, where customers at Indomaret Sirojudin showed a tendency to switch to competitors, even though the store has the highest customer rating. This study aims to analyze the influence of brand image, customer experience, and service quality on customer loyalty at Indomaret Sirojudin, Semarang. The research employed a quantitative approach using purposive sampling with 100 respondents. The measurement scale used was a 4-point Likert scale. Data analysis was conducted through validity and reliability tests, normality, heteroscedasticity, multicollinearity, linearity tests, t-test, F-test, coefficient of determination, and multiple linear regression using SPSS 26. The results indicate that brand image does not significantly affect customer loyalty, while customer experience and service quality have a significant positive influence. The resulting regression equation is: Y = 0.920 + 0.291X₂ + 0.543X₃. These findings highlight that shopping experience and service quality are the two most influential factors in driving customer loyalty in retail contexts.